New Cost‐Effective Halide Solid Electrolytes for All‐Solid‐State Batteries: Mechanochemically Prepared Fe3+‐Substituted Li2ZrCl6. Issue 12 (18th January 2021) - Kwak, Hiram; Han, Daseul; Lyoo, Jeyne; Park, Juhyoun; Jung, Sung Hoo; Han, Yoonjae; Kwon, Gihan; Kim, Hansu; Hong, Seung‐Tae; Nam, Kyung‐Wan; Jung, Yoon Seok
Abstract: Owing to the combined advantages of sulfide and oxide solid electrolytes (SEs), that is, mechanical sinterability and excellent (electro)chemical stability, recently emerging halide SEs such as Li3 YCl6 are considered to be a game changer for the development of all‐solid‐state batteries. However, the use of expensive central metals hinders their practical applicability. Herein, a new halide superionic conductors are reported that are free of rare‐earth metals: hexagonal close‐packed (hcp) Li2 ZrCl6 and Fe 3+ ‐substituted Li2 ZrCl6, derived via a mechanochemical method. Conventional heat treatment yields cubic close‐packed monoclinic Li2 ZrCl6 with a low Li + conductivity of 5.7 × 10 −6 S cm −1 at 30 °C. In contrast, hcp Li2 ZrCl6 with a high Li + conductivity of 4.0 × 10 −4 S cm −1 is derived via ball‐milling. More importantly, the aliovalent substitution of Li2 ZrCl6 with Fe 3+, which is probed by complementary analyses using X‐ray diffraction, pair distribution function, X‐ray absorption spectroscopy, and Raman spectroscopy measurements, drastically enhances the Li + conductivity up to ≈1 mS cm −1 for Li2.25 Zr0.75 Fe0.25 Cl6 . The superior interfacial stability when using Li2+ x Zr1− x Fe x Cl6, as compared to that when using conventional Li6 PS5 Cl, is proved. Furthermore, an excellent electrochemical performance of the all‐solid‐state batteries is achieved via the combination of Li2 ZrCl6 and single‐crystalline LiNi0.88 Co0.11 Al0.01 O2 . Abstract : New cost‐effective rare‐earth‐metal‐free halide superionic conductors for all‐solid‐state batteries are developed. In contrast to poorly Li + ‐conductive cubic close‐packed monoclinic Li2 ZrCl6 produced by heat‐treatment, ball‐milling leads to an hexagonal close‐packed structure and high Li + conductivity (0.40 mS cm −1 ). The Fe 3+ ‐aliovalent substitution further enhances the Li + conductivity reaching ≈1 mS cm −1 . The outstanding performance of LiCoO2 and single‐crystalline LiNi0.80 Co0.11 Al0.01 O2 employing Li2+ x Zr1− x Fe x Cl6 are also demonstrated.